Evolutionary Study of Three Decades Literatures Related to Disaster Management Agency and Public Policy: A Bibliometric Study - Kurniawati, Chandra Puspita; Muhtar, Entang Adhy; Pancasilawan, Ramadhan (TDMRC, Universitas Syiah Kuala, 2023)
This study is aimed at examining scientific literatures written by international authors focusing on disaster management agency topic that are related to public policy from the first paper published in 1995 to 2022 using bibliometric study employing a database from Scopus. To visualize the results, this study utilizes VOSviewer version 1.6.17. The results showed that this topic emerged in Thailand which focused on roles of local level disaster management agency in carrying out rehabilitation and reconstruction activities in district level. However, Federal Emergency Management Agency, or the United States Disaster Management Agency, was considered to be the most researched disaster management agency. Besides, open-access social science articles dominated the type of publications in this research area. Moreover, the United States and its authors were perceived as the most productive and influential country and authors. Meanwhile, the United Kingdom was recognized as the most influential sources title with Journal Disasters served the most productive and influential source title. Besides, the affiliation among Austria, Nigeria, South Africa, and the United States were acknowledged as the most productive and influential affiliations. The analysis also indicated that this topic developed and strongly connected to disaster and disaster management research areas. Considering the comprehensive nature of bibliometric analysis, this study may help scholars get a broad view of the relevant issues, while at the same time identifying reputable publications worth studying for reference.